2021
DOI: 10.11114/bms.v7i2.4924
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Corporate Social Responsibility to Companies During Turbulent Economic Times: A Survey of Zimbabwe Stock Exchange Listed Companies

Abstract: Corporate Social Responsibility (CSR) has remained topical and contentious as various schools of thought are put forward on its relationship to cost versus profitability for businesses. This study explored the relevance of CSR and its effect on the survival of businesses during an economic meltdown in Zimbabwe. The study purposively sampled 31 companies that are listed on the Zimbabwe Stock Exchange and have sound CSR programmes. A total of 93 questionnaires were administered and a Chi-square was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several studies focused on developing and emerging economies (Hackston & Milne, 1996;Gelb & Strawser, 2001;Ali, Frynas, & Mahmood, 2017;Laskar & Maji, 2017) whilst others were conducted in developed economies (Branco & Rodrigues, 2008;Reverte, 2009;Gamerschlag, Möller, & Verbeeten, 2011;Barakat et al, 2015;Ali et al, 2017). Some studies from an international perspective examined CSRVD of firms in the same type of industry (Chih et al, 2010;Li & Zhang, 2010;Medrado & Jackson, 2016;Laskar & Maji, 2017) in addition, the majority of studies from Zimbabwe examined CSR in different single industries or in different single sectors for instance, Menenji (2018) investigated the impact of CSR practices on employee motivation and performance in the telecommunications sector, Magaya & Nhavira (2016) studied CSR in the construction industry, Murombo (2016) studied CSR in the extractive sector, Dlamini & Mavengere (2019) investigated CSR disclosure and firm performance in the banking sector and established an insignificant negative relationship, Chanakira, M., & Masunda (2019) reviewed CSR engagement in the SMEs sector, Mlilo (2018) examined CSR and firm performance in the insurance industry whilst Makanyeza et al (2018) examined dimensions of CSR and firm performance in all industries, however these dimenions were not linked to disclosure ; Sibanda et al (2021) investigated CSR strategies and business survival and concluded that different strategies are required for different industries, whilst Mathende & Nhapi (2017) undertook a study to conceptualisation and understand the determinants of CSR whilst 196 exploring the experiences of communities.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on developing and emerging economies (Hackston & Milne, 1996;Gelb & Strawser, 2001;Ali, Frynas, & Mahmood, 2017;Laskar & Maji, 2017) whilst others were conducted in developed economies (Branco & Rodrigues, 2008;Reverte, 2009;Gamerschlag, Möller, & Verbeeten, 2011;Barakat et al, 2015;Ali et al, 2017). Some studies from an international perspective examined CSRVD of firms in the same type of industry (Chih et al, 2010;Li & Zhang, 2010;Medrado & Jackson, 2016;Laskar & Maji, 2017) in addition, the majority of studies from Zimbabwe examined CSR in different single industries or in different single sectors for instance, Menenji (2018) investigated the impact of CSR practices on employee motivation and performance in the telecommunications sector, Magaya & Nhavira (2016) studied CSR in the construction industry, Murombo (2016) studied CSR in the extractive sector, Dlamini & Mavengere (2019) investigated CSR disclosure and firm performance in the banking sector and established an insignificant negative relationship, Chanakira, M., & Masunda (2019) reviewed CSR engagement in the SMEs sector, Mlilo (2018) examined CSR and firm performance in the insurance industry whilst Makanyeza et al (2018) examined dimensions of CSR and firm performance in all industries, however these dimenions were not linked to disclosure ; Sibanda et al (2021) investigated CSR strategies and business survival and concluded that different strategies are required for different industries, whilst Mathende & Nhapi (2017) undertook a study to conceptualisation and understand the determinants of CSR whilst 196 exploring the experiences of communities.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the SMEs sector in Zimbabwe has grown in importance as a source of income a large number of families in both rural and urban places (Muruviwa et al, 2018;Mugova and Sachs, 2019). CSR is a way of managing consumer interactions, it tackles environmental and societal problems, it is a result of community pressure, it is a way of creating a positive business image, and it is a tool for making employees happy and pleased in Zimbwabwe (Sibanda et al, 2021). Zimbabwe's economy does not support social solidarity across the country (Manuere;Kennedy Nyahunzvi, 2013;Makanyeza et al, 2018;Wong et al, 2021).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%